Mechanisms Mediating Spinal and Bulbar Muscular Atrophy: Investigations into Polyglutamine-Expanded Androgen Receptor Function and Dysfunction - Beitel, Lenore K.; Alvarado, Carlos; Mokhtar, Shaza; Paliouras, Miltiadis; Trifiro, Mark (Frontiers in Neurology, 2013)
Spinal and bulbar muscular atrophy (SBMA, Kennedy’s disease), a late-onset neuromuscular disorder, is caused by expansion of the polymorphic polyglutamine tract in the androgen receptor (AR). The AR is a ligand-activated transcription factor, but plays roles in other cellular pathways. In SBMA, selective motor neuron degeneration occurs in the brainstem and spinal cord, thus the causes of neuronal dysfunction have been studied. However, pathogenic pathways in muscles may also be involved. Cultured cells, fly and mouse models have been used to study the molecular mechanisms leading to SBMA. Both the structure of the polyglutamine expanded AR (polyQ AR) and its interactions with other proteins are altered relative to the normal AR. The ligand-dependent translocation of the polyQ AR to the nucleus appears to be critical, as are interdomain interactions. The polyQ AR, or fragments thereof, can form nuclear inclusions, but their pathogenic or protective nature is unclear. Other data suggests soluble polyQ AR oligomers can be harmful. Post-translational modifications such as phosphorylation, acetylation, and ubiquitination influence AR function and modulate the deleterious effects of the polyQ AR. Transcriptional dysregulation is highly likely to be a factor in SBMA; deregulation of nongenomic AR signaling may also be involved. Studies on polyQ AR protein degradation suggest inhibition of the ubiquitin proteasome system and changes to autophagic pathways may be relevant. Mitochondrial function and axonal transport may also be affected by the polyQ AR. Androgens, acting through the AR, can be neurotrophic and are important in muscle development; hence both loss of normal AR functions and gain of novel harmful functions by the polyQ AR can contribute to neurodegeneration and muscular atrophy. Thus investigations into polyQ AR function have shown that multiple complex mechanisms lead to the initiation and progression of SBMA.